2021
DOI: 10.1002/hep.31489
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Regression of Hepatocellular Carcinoma: When the Immune System Stands Up to Cancer

Abstract: pontaneous regression of cancer is rare and has been observed mostly in immunogenic cancers like melanoma. A few cases of spontaneous regression of hepatocellular carcinoma (HCC) have been reported, but the mechanisms of regression have not been elucidated. Here, we report a patient with advanced HCC who experienced spontaneous regression of her tumor and present evidence for a putative immune-mediated mechanism for tumor regression. Case SeriesThe index patient is a 65-year-old female patient with alcohol-ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…Arjunan et al. [6] recently reported that a patient with HCC showing spontaneous regression showed altered immunological subsets including extremely high CD16+ NK cell and CD16+ monocyte levels and strongly suggested host-immune participation for the tumor regression in HCC. At 3 months after TACE with RFA, percentages of CD16+ NK cells and CD16+ monocytes, assayed by flow cytometry, were extremely high in this case, which was consistent with their report [6] .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Arjunan et al. [6] recently reported that a patient with HCC showing spontaneous regression showed altered immunological subsets including extremely high CD16+ NK cell and CD16+ monocyte levels and strongly suggested host-immune participation for the tumor regression in HCC. At 3 months after TACE with RFA, percentages of CD16+ NK cells and CD16+ monocytes, assayed by flow cytometry, were extremely high in this case, which was consistent with their report [6] .…”
Section: Discussionmentioning
confidence: 97%
“…However, spontaneous cancer regression has been sporadically described in various cancer types and defined as partial or complete disappearance of a malignant tumor without specific treatments [1] . Spontaneous regression of hepatocellular carcinoma (HCC) has also been reported [2] , [3] , [4] , [5] , though extremely uncommon and reported as 0.1%-0.4% [3 , 6] . Several reports [7] , [8] , [9] , [10] described that spontaneous regression of lung metastases of HCC.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a recent case report implicated enrichment of CD16+ NK cells in one patient with advanced HCC that spontaneously regressed. 6 Our patient's tumor exhibited a high TMB (Table 1). TMB is at least partially independent from other immunotherapy biomarkers-such as programmed death-ligand 1 11 and microsatellite instability 12 -and is associated with a primed immune system that is poised to respond to immune checkpoint inhibition in multiple cancer types.…”
Section: Discussionmentioning
confidence: 79%
“…There have been several case reports and case series demonstrating radiographic and/or pathologic evidence of spontaneous HCC regression, even at an advanced stage and sometimes completely. 6 , 8 In those instances, there was no documentation or report of the TMB status. The assembled case series that document such regression have often invoked inflammatory stimuli or other systemic or physiologic perturbations to explain the antitumor effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation